Mechanisms of interfacial bond in steel and polypropylene fiber reinforced geopolymer composites. (18th January 2016) - Ranjbar, Navid; Talebian, Sepehr; Mehrali, Mehdi; Kuenzel, Carsten; Cornelis Metselaar, Hendrik Simon; Jumaat, Mohd Zamin
Abstract: The fiber-matrix interface properties play an important role in determining the overall mechanical performance of the fiber reinforced brittle matrix composites. This study is to evaluate the effects of wettability, chemical characterization and nanometric roughness of two different fibers, polypropylene (PPF) and micro steel fibers (MSF), superposed by shrinkage of fly ash based geopolymer binder on fiber-matrix interaction and the consequent mechanical properties of the corresponding composites. The fiber incorporation in geopolymer matrix was performed by 0.5, 1, 2, 3 and 4% of the total volume of each type of fibers. The results show that MSF has strong contact with the geopolymer paste since it tends to behave as a hydrophilic material that resulted in significant improvement in energy absorption and flexural strength of the composite; while PPF led to fiber-matrix debonding due to hydrophobic characteristics of the fiber compounds by geopolymer shrinkage that weakened the mechanical performances of the composites.